Utilization of Dynamical System on Enfolding Semi-group - Ridha, Haider M.; Majed, Lieth A.; Al-Fayadh, Ali Hassan Nasser (Iraqi Journal of Science, 2023)
In this paper, we use  the definition of the action on the set of semi-group of the structure of this research .We introduce the concepts of  -system which is a triple , ,  such that  is a Hausdorff compact space called  phase space,  is a semi-group of transformations with a continuous action  of   on  . We study and proof some theoretical properties related with that system. We also introduce the concept of Enfolding semi-group ( , ,and we prove that it is a compact right topological semi-group. In addition, we study the left and right ideals in the Enfolding semi-group. By using the dynamical system, we reflect various properties concerning with its structure for the Enfolding semi-group. Furthermore, we describe the connections between the algebraic and topological properties of the Enfolding semi-group space.